Grip Strength and Demographic Variables Estimate Appendicular Muscle Mass Better Than Bioelectrical Impedance in Taiwanese Older Persons - Hsiao, Ming-Yen; Chang, Ke-Vin; Wu, Wei-Ting; Huang, Kuo-Chin; Han, Der-Sheng (Journal of the American Medical Directors Association, 2021)
This study aimed to develop an equation model combining physical fitness and anthropometric parameters and compare its results with those of bioelectrical impedance analysis (BIA)-measured lean mass (LM) using dual-energy X-ray absorptiometry (DXA)-measured appendicular muscle mass (AMM) as reference. Observational analysis. Healthy community-dwelling older subjects. A total of 1020 participants were randomly allocated to the development group (development group, n = 510) or the cross-validation group (validation group, n = 510). Body composition was measured using both DXA and BIA, and physical fitness parameters, including grip strength, timed stepping test, sit-to-stand test, flexibility, and walking speed were also assessed. A prediction equation model of AMM by stepwise linear regression analysis that included or excluded 1 independent variable at each step, based on the P value of significance (P < .05), was developed. Using weight, sex, height, and handgrip strength as independent variables, the equation AMM = -9.833 + 0.397 × weight (kg) + 4.433 × sex + 0.121 × height (cm) + 0.061 × handgrip strength (kg) best predicts DXA-measured AMM (adjusted R = 0.914, SEE = 2.062, P < .001). The predicted AMM was more highly correlated with DXA-measured AMM than the commonly used BIA-measured LM (R = 0.9158 and 0.8427, respectively, both P < .001). Using DXA-measured AMM as reference, the Bland-Altman plot showed mean differences of -0.03 kg and -0.12 kg, with limits of agreement of -3.98 to 3.92 kg and -5.97 to 5.73 kg for the predicted AMM and BIA-measured AMM, respectively. The proposed equation offers a practical alternative method for estimating AMM that is less facility-dependent and more easy to use and affordable than instrumental studies.